EFFECT OF VERMICOMPOST AND SULPHUR ON GROWTH, YIELD AND NUTRIENT UPTAKE OF FENUGREEK (TRIGONELLA FOENUMGRAECUM L.) - S. R. VERMA; A. C. SHIVRAN; R. BHANWARIA; M. SINGH (The Bioscan, 2014)
A field experiment was conducted during Rabi season of 2011-2012 at Jobner (Rajasthan) to study the effect of vermicompost and sulphur on growth, yield and nutrient uptake of fenugreek. The experiment consisting of sixteen treatment combinations with four levels of vermicompost (0, 2, 4, and 6 t ha-1) and four levels of sulphur (0, 20, 40, and 60 kg ha-1) was laid in randomized block design with three replications. Application of vermicompost up to 4 t ha-1 significantly increased plant height (34.05, 50.2 and 58.9 cm), branches/plant (3.69, 5.73 and 8.06) at 60, 90 DAS and at harvest, total (26.22) and effective root nodules (14.95), leghaemoglobin content in root nodules (1.94 mg g-1), seed (15.26 q ha-1) and straw yields (39.02 q ha-1), net returns (34235 Rs ha-1) total uptake of N (4.49 kg ha-1), P (0.699 kg ha-1), K (3.29 kg ha-1) and S (0.494 k ha-1) over lower levels. However, available nitrogen (140.71 kg ha-1) status of soil after crop harvest was significantly increased with vermicompost up to 6 t ha-1 vermicompost 4 t ha-1 increased seed yield by 25.00 and 9.45 percent and net returns by 12.60 and 3.95 percent over control and 2 t ha-1 vermicompost, respectively. Results further indicated that application of sulphur up to 40 kg ha-1 resulted in significantly higher plant height(34.06, 50.2 and 59.0 cm) and branches/plant (3.53, 5.67 and 8.00) at 60, 90 DAS and at harvest, total (27.06) and effective root nodules (15.00), leghaemoglobin content in root nodules (1.91 mg g-1), seed (15.05 q ha-1) and straw yields (38.80 q ha-1), net returns (35311 Rs ha1), total uptake of N (4.48 kg ha-1), P (.683 kg ha-1), K (3.29 kg ha-1) and S (0.497 Kg ha-1) and available Nitrogen (140.97 kg ha-1) content in soil after crop harvest over lover levels of sulphur application. The application of 40 kg ha-1 sulphur increased seed yield by 29.10 and 11.55 percent and net returns by 36.55 and 12.40 percent, respectively, over control and 60 kg S ha-1.